Exploring Online Health Information-Seeking Behaviours among Older Adults in Rural Areas - Park, Hyejin; Tseng , HuiChen; Park, Minsook (Technium Social Sciences Journal, 2021)
Little is known about use of internet and online health information seeking behaviours of older adults who live in rural area. This study explored technology use, online health information-seeking behaviours among older adults in rural areas, and then identified differences of technology use and online health information seeking behaviours between urban and rural areas. Secondary data from Pew Research Institute’s Information Engaged and Wary Survey data were used. In this study, 775 participants aged 65 or older were included in the data analysis. To determine differences in health information seeking behaviours among older adults between urban and rural areas, first chi-square test and Fisher’s exact test were used to assess differences in demographic variables between older adults in urban and rural areas, and then t-tests were used to determine any differences regarding use of Internet and online information-seeking behaviours between urban and rural areas. Older adults in rural communities used the Internet and email slightly less than older adults in urban areas. Older adults in rural areas needed much more help finding the information they need online compared to urban older adults. Based on the results, appropriate or individualized supports should be provided to older adults, especially those in rural areas, to help them obtain reliable online health information to support better decisions about their health.